The Impact of ICT on Vegetable Farmers in Honduras - Allan Pineda; Marco Aguero; Sandra Espinoza (Inter-American Development Bank (IDB), 2011)
Honduran farmers are at a disadvantage when dealing with intermediaries because they lack timely information about market prices. This paper first analyzes which information and communications technology (ICT) would be most suitable for sending price information to producers scattered throughout the country at a reasonable cost and in a sustainable way. Negotiations by two groups of farmers were compared: one to which market prices were not sent (control) and one to which prices were sent (treatment). A simple uninterrupted time series research design was used, followed by linear regression analysis and univariant analyses to determine the cases in which the treatment had an impact on farmers negotiations. Findings are reported, as well as recommendations and lessons learned.
Keywords: D24; O33; Q12; Q13; 330